The role of organizational semiotics and its implications for the development of organizational architecture: An empirical study in the directorate of quality assurance at the university of Sulaimani - Salah Hamasaeed Hamasaleh; Halat Saeed Hamasalah (QALAAI ZANIST SCIENTIFIC JOURNAL, 2020)
The main objective of the research is to know the role of Organizational Semiotics in its Dimensions Represented by (Behavioral standards, Perceptual standards, Conceptual standards, Evaluation standards) in developing the Organizational Architecture and its dimensions represented by (Organizational Structure, Organizational Culture, Technology, Strategic Plan).This is in an attempt to address a realistic problem that directly affects Quality Assurance at the University of Sulaimani, and a hypothetical outline of the research was designed that expresses the main assumptions, and the Electronic Questionnaire was used as a tool for data collection, and it was Distributed to (70) Affiliates in the Quality Assurance Directorate at the University of Sulaimani and its affiliated units in the colleges . (51) Valid questionnaires were retrieved for analysis, and the response rate was (%73). In order to verify the correctness of the hypotheses, it was put to multiple tests using the Statistical Program (SPSS V.26). The research followed the descriptive and analytical approach, and reached a number of Conclusions, The most important of which is the Impact of Organizational Semioticism with its standards used in Developing the Organizational Architecture of the Quality Assurance Directorate at the University of Sulaimani and its colleges units. Based on that, the researchers presented a set of Recommendations consistent with these Conclusions for the purpose of benefiting from them by the researched university, the most important of which is the need to focus on the basic standards in organizational semiotics that directly and significantly affect the creation of added value in the university in terms of its Organizational Architecture.